LESSON LEARNED BERDASARKAN BEST PRACTICE PEMUNGUTAN CUKAI ATAS MINUMAN BERPEMANIS DALAM KEMASAN DI FILIPINA - Dipinto, Ryan Nanda Putra; Setyowati, Milla Sepliana (JURNAL PERSPEKTIF BEA DAN CUKAI, 2024)
The imposition of excise tax on sweetened beverages (SSBs) in the Philippines aims to reduce excessive sugar consumption, which contributes to the increasing cases of obesity and non-communicable diseases such as diabetes. This study analyzes the best practices of implementing the excise tax on SSBs in the Philippines, which can serve as a reference for other countries, including Indonesia, using a qualitative method with literature review. The results show that the success of this policy is influenced by strong government commitment, support from various parties, and the simplicity of implementing the excise tax policy. Furthermore, this policy has been able to encourage changes in consumer behavior and product reformulation by the industry. With good collaboration between the government and food regulators, the excise tax is expected to contribute to the long-term improvement of public health. This study recommends that Indonesia adopt a similar excise tax policy, considering local conditions and inter-agency cooperation to ensure the policy's success.